Decreased insulin sensitivity and increased oxidative damage in wasting adipose tissue depots of wild-type mice - Sackmann-Sala, Lucila (Springer Netherlands, 2011)
Unintentional weight loss (wasting) in the elderly is a major health concern as it leads to increased mortality. Several studies have focused on muscle loss, but little is known about the mechanisms giving rise to loss of fat mass at old ages. To investigate potential mechanisms, white adipose tissue (WAT) characteristics and proteomic profiles were compared between adult (10–12-month-old) and aged (22–24-month-old) wild-type mice. Four individual WAT depots were analyzed to account for possible depot-specific differences. Proteomic profiles of WAT depots, along with body weights and compositions, plasma levels of insulin, leptin and adiponectin, insulin tolerance, adipocyte sizes, and products of oxidative damage in each WAT depot were determined. We found that lean mass remained constant while fat mass and insulin tolerance were decreased in old age, as were adipocyte sizes in the WAT depots. Proteomic results showed increased levels of enolase, pyruvate dehydrogenase E1β, NAD(+)−dependent isocitrate dehydrogenase α, and ATP synthase subunit β, and decreased levels of carbonic anhydrase 3 in WAT of aged mice. These data suggest increased aerobic glucose oxidation in wasting WAT, consistent with decreased insulin signaling. Also, Cu/Zn superoxide dismutase and two chaperones were increased in aged WAT depots, indicating higher stress resistance. In agreement, lipid peroxidation (HNE-His adducts) increased in old age, although protein oxidation (carbonyl groups) showed no increase. In conclusion, features of wasting WAT were similar in the four depots, including decreased adipocyte sizes and alterations in protein expression profiles that indicated decreased insulin sensitivity and increased lipid peroxidation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11357-011-9304-7) contains supplementary material, which is available to authorized users.